The progress of molecules and strategies for the treatment of HBV infection - Pan, Youlu; Xia, Heye; He, Yanwen; Zeng, Shenxin; Shen, Zhengrong; Huang, Wenhai (Frontiers in Cellular and Infection Microbiology, 2023)
Hepatitis B had already been a heavy burden of mortality. In 2019, hepatitis B virus (HBV)-related diseases approximately resulted in 555,000 deaths in global. In view of the high lethality, the treatment of HBV had already been a huge challenge. The World Health Organization (WHO) came up with ambitious targets for elimination hepatitis B as a major public health threat by 2030. To accomplish this goal, one of the WHO's strategies was to develop curative treatment for HBV infection. Current treatments in clinical included 1 year of pegylated-interferon-α (PEG-IFNα) and long-term nucleoside analogues (NAs). Although both of them had achieved outstanding antiviral effects, it was difficult to obtain HBV cure. Actually, covalently closed circular DNA (cccDNA), integrated HBV DNA, the high viral burden and the impaired host immune responses limited the cure of HBV. In order to overcome these problems, there were already a number of antiviral molecules showing the promising results and in the clinical study. In this review, we summarized various synthetic molecules, natural products, traditional Chinese herbal medicines, CRISPR/Cas, ZFNs, and TALENs, which could destroy the stability of HBV life-cycle. Additionally, we summed up immune modulators that can enhance or activate the host immune system. Furthermore, we also introduced some representative natural products with anti-HBV effects.